Cultural competence education for undergraduate medical students: An ethnographic study - Liu, Jia; Miles, Katherine; Li, Shuangyu (Frontiers in Education, 2022)
The COVID-19 pandemic and the escalation of the Black Lives Matter Movement worldwide have foregrounded the long-standing inequality in society and healthcare. The provision of culturally competent care has become more necessary than at any other time. However, cultural competence (CC) education remains inconsistent across medical schools, and little is known about how students develop their CC through campus-based classroom teaching. We took an ethnographic approach to study students’ development of CC in campus-based formal classroom teaching. This study was conducted in a large London medical school in England. We triangulated data collected from six-month participant observation, 25 individual interviews, and three focus groups to generate reliable accounts of students’ CC developmental experience. Thick descriptions were developed through iterative, inductive, interactive, and reflexive review and interpretation of data using NVivo 11. The results show that students undergo staged cultural learning throughout their undergraduate medical curriculum through bespoke CC lectures, workshops, clinical/research projects, and integrated clinical simulations that incorporate CC and other clinical subjects. The early learning mainly takes place in the pre-clinical year of the curriculum, among which a range of valued-based sessions is observed as conducive to students’ development of CC. As they progress, students develop their CC by attending clinical sessions with embedded cultural content. The curriculum in senior years presents reduced mandatory teaching, but more clinical exposure and opportunities to reach out to other subjects and disciplines. It means students start to have more diverse and dispersed learning experiences based on their individual choices, some of which may contribute to their development of CC. This study provides a rare insight into medical students’ CC development through participation in campus-based classroom teaching. Various learning opportunities contribute to different aspects of CC development and cater to different learning preferences of the diverse student population. To support students’ comprehensive development of CC, educators need to work collaboratively and use overt signposting to related disciplines and subjects. There needs to be recognition of students’ learning not only in the formal curriculum but also in the informal and hidden curricula.